Elaboración de un plan de negocio para la creación de un emprendimiento tu mejor estilo hecho solo para mujeres en la ciudad de Palmira - Castro Gómez, Natalia; Castro Gómez, Veronica (Universidad Antonio Nariño, 2023)
The document that is listed below contains the implementation of a Business Plan to measure the commercial, technical, administrative, legal and financial feasibility of setting up a business for the commercialization of imported and national garments in a Boutique store.